(untitled) (Research Announcements "Heritage BG", 2025)
Interpreting individual texts by Rada Kirkovich, this article problematizes important aspects of women’s epistolary and journalistic texts in the nineteenth century about the slow steps towards women’s emancipation. In these appearances, the prominent role of the educated woman within the strictly regulated boundaries of Bulgarian Revival publicity becomes more apparent. Adherence to these patterns of opening helped to gradually shape the modern-minded individual with her new social role. The Revival woman is enthralled by a new model standing alien to the traditional patriarchal society. The analysis of the post-liberation book “Memories” (1927) by R. Kirkovich allows us to trace the more marginal place of the female figures about the visible role of prominent Bulgarian and Russian public figures during the Renaissance. Through her autobiography, the writer constructs women’s history – exemplars of a new type of cultural presence in the 19th century. Archives: NBKM BIA. Fond 22 (Nayden Gerov). op. I, a. e. 595, 29–32b. NBKM BIA. Fond 22. op. I, a. e. 190, 1–29. Primary sources: D. G. 1873: D. G. [Initials of Kirkovich, Rada]. Gosp. Redaktore! na v. Pravo!. – Pravo, VIII, 5, 14.04.1873, 3–4. IANG 1911: Iz arhivata na Nayden Gerov. Pisma, dokladi i materiali za vazrazhdaneto na balgarskia narod. Korespondentsia s chastni litsa. Kn. 1. Pod red. na Todor Panchev. Sofia. Kirkovich 1873: Kirkovich, Rada. Dve pisma. Mila Spaske. – In: Balgarskiy kalendar za 1874 godina. Plovdiv, 53–58. Kirkovich 1927: Kirkovich, Rada. Spomeni. Sofia. Spaska 1874: Spaska. Dve pisma. Pochitaema G-zhe Rado. – Balgarskiy kalendar za 1874 godina. Plovdiv, 50–52. Secondary sources: Aretov 2006: Aretov, Nikolay. Natsionalna mitologia i natsionalna literatura. Syuzheti, izgrazhdashti balgarskata natsionalna identichnost v slovesnostta ot XVIII i XIX vek. Sofia. Gandhi 2005: Gandhi, Liyla. Postkolonialna teoria. Kritichesko vavedenie. Sofia. Damyanova 1995: Damyanova, Rumyana. Pismata v kulturata na Balgarskoto vazrazhdane. Shumen. Daskalova 1995: Daskalova, Krasimira. Feminizmat, istoriyata na zhenite i ramkite za tyahnoto osmislyane. – Sotsiologicheski problemi, 4, 5–15. Kalinova 2012: Kalinova, Maria Detstvo i intelektualna istoria u vazrozhdenskite avtori. Sofia. Kapralova 1999: Kapralova, Nedka. Za etiketa i zad nego (kakvo razkazvat i razkrivat pismata ot zapania lichen arhiv na semeystvo Karaminkovi). – In: Mayki i dashteri. Pokolenia i posoki v balgarskia feminizam. Sofia, 139–152. Nalbantova 2001: Nalbantova, Elena. Vazrozhdenskiyat chovek – utopii i realnosti. Veliko Tarnovo. Bock 1991: Bock, Gisela. Challenging Dichotomies: Perspectives on Women’s History. – In: Writing Women’s History: International Perspectives. Bloomington, 1991, 1–24.